Radiation Exposure Knowledge among Anaesthesia Residents: A Cross Sectional Study in Karachi Teaching Hospitals - Nasiruddin, Asir; Adeel Ur Rehman; Naeem , Kashif; Lawrence , Atif Pervaiz; Ahmed , Syed Faraz (Indus Journal of Bioscience Research, 2025)
Introduction: Preventive strategies to reduce radiation-induced harm among anaesthesiologists are directed by the National Council on Radiation Protection and Measurements and the US Environmental Protection Agency. These instructions underscore the necessity of minimising exposure intensity and duration, maintaining distance from the radiation source, and employing shielding against both primary and dispersed radiation. This study sought to assess the knowledge and apprehension of radiation exposure among anaesthesia residents in teaching hospitals in Karachi via an online questionnaire. Objective: To evaluate the understanding of radiation exposure and protective protocols among anaesthesia residents in teaching hospitals in Karachi. Method: A cross-sectional study was performed at many teaching hospitals in Karachi, including The Indus Hospital, AKUH, Ziauddin Hospital, Civil Hospital, JPMC, NICVD, LNH, and Abbasi Shaheed Hospital. The research was conducted during a six-month period, from January 6, 2023, to July 5, 2023, subsequent to the endorsement of the research Participants who satisfied the inclusion criteria submitted written informed consent. An online questionnaire, self-administered via Google Forms, gathered data on knowledge regarding radiation exposure. All responses were recorded electronically for analysis. Result: The study comprised residents aged 24 to 50 years, with a median age of 29 years. Of the 119 participants, 79 (66.4%) were male, while 40 (33.6%) were female. Merely 10 residents (8.4%) exhibited sufficient understanding of radiation exposure and preventative strategies. Conclusion: This study demonstrated a minimal proportion of anaesthesia residents have sufficient information regarding radiation exposure and safety protocols.